Don’t worry, be happy: enhancing the positive mood of older adults and investigating influenza vaccination responses - Brown, Michaela (2022)
Vaccinations are vital for reducing the risk of disease, where they play an important role in combating influenza. However, some populations, such as older adults (≥65 years), respond poorly to influenza vaccination due to their compromised immune systems, with efficacy at 17-53% compared to 70-90% in young adults. This is a phenomenon referred to as immunosenescence, whereby older adults have sub-optimal immune systems and are therefore more susceptible to infectious disease. The burden of influenza is becoming an increasingly important challenge to tackle with the rapidly ageing population in the UK. Every year the UK experiences 4,000 to 14,000 deaths due to influenza, where a staggering 90% of these are older adults.